Inclusive Mathematics Education: An Introduction - Kollosche, David; Marcone, Renato; Knigge, Michel; Penteado, Miriam Godoy [UNESP]; Skovsmose, Ole [UNESP] (Springer Nature, 2019)
Inclusion has become a global topic in education and educational studies. This introduction briefly recapitulates the idea of inclusion and the essential steps in this development.
Keywords: Diversity; Inclusion; Inclusive education; Special needs